Stakeholder requirements for goods transportation decarbonization – An examination of transportation chains - Eriksson, Taina; Ertiö, Titiana; Khan, Fuad (Elsevier, 2026)
This study aims to understand decarbonization opportunities in a transportation chain as a collaborative effort of multiple stakeholders, each of whom have different requirements to meet. While transportation providers aim to reduce emission for their own mode, transportation customers seek to decarbonize their multi-modal transportation chain. Enablers, on the other hand, develop and supply emission reduction technologies to cater all transportation modes. We investigate stakeholders’ requirements as a prerequisite for value creation at the transportation chain level. The study employs the Jobs-to-be-done theory to uncover requirements for value creation. 18 semi-structured interviews have been analyzed using theoretical coding then subsequently data-driven coding for a qualitative content analysis approach. While all stakeholders share an overarching goal of decarbonization, balancing their requirements with cooperation efforts is perceived as a necessary step to create value, benefit from reductions and share the risks and costs associated with emission reduction efforts. This study investigates the requirements for decarbonization at a transportation value chain level. By applying the Jobs-to-be-done framework in a B2B context, the study uncovered mutual reliance jobs, which extend our understanding of value creation opportunities. We derive several managerial implications for operationalizing emission reduction solutions, with an emphasis on removing barriers for purchasing low-emission transportation services.